The effect of hyaluronic acid on the skin healing in rats - Medeiros Soares Celani, Livia; Soares Lopes, Isadora; Cunha Medeiros, Aldo (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2019)
Purpose: The objective of this study was to examine the effect of topical hyaluronic acid (HA) treatment on wound healing in rats. Methods: Wistar rats were randomly selected and allocated into 2 groups, with six rats each, all of them submitted to skin lesions (open wound with 5mm diameter). Group 1 – rats treated with topical 0,9% saline application in skin wounds. Group 2 – rats treated with topical hyaluronic acid 0,4% on skin wounds once a day for 7 days. After anesthesia on the 7th postoperative day, a biopsy of the skin dorsal wound area was performed for histopathological examination. A classification system based on the degree of reepithelization, granulation tissue formation and collagen organization were used to relate the morphological differences in wound healing. Results: Rats from control group treated with saline solution, on day 7, presented a general impairment of healing process, marked by an incomplete reepithelization (score 2,67 ± 0,4), a persistent exudation, fibrin, reduced accumulation of granulation tissue (score 2,2 ± 0,5) and a slight collagen deposition (score 2,43 ± 0,5), compared with the HA group. On the other side, morphological differences were visible on the evolution of wound repair process in rats treated with HA with a significant reduction in fibrinous exudation, epidermal lining reconstitution by complete reepithelization (score 3,8 ± 0,6), an increased accumulation of granulation tissue at wound edge and bed (score 3,7 ± 1,1), moderate collagen deposition (3,8 ± 0,7). The respective differences between the groups were significant (p<0,05). Conclusions: Based on these findings, we may conclude that HA treatment contributes to improve healing of open wounds.